2023
DOI: 10.1021/acsami.3c00537
|View full text |Cite
|
Sign up to set email alerts
|

Fully Microfabricated Surface Acoustic Wave Tweezer for Collection of Submicron Particles and Human Blood Cells

Abstract: Precise manipulation of (sub)micron particles is key for the preparation, enrichment, and quality control in many biomedical applications. Surface acoustic waves (SAW) hold tremendous promise for manipulation of (bio)particles at the micron to nanoscale ranges. In commonly used SAW tweezers, particle manipulation relies on the direct acoustic radiation effect whose superior performance fades rapidly when progressing from micron to nanoscale particles due to the increasing dominance of a second order mechanism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Both surface acoustic waves (SAWs) and ultrasonic standing waves (USWs) can be used for nano/micromotor manipulation. SAWs usually use piezoelectric ceramics (such as lithium niobate, LiNbO3) as the substrate with interdigital transducers (IDTs) on the surface (Figure 3A,B) [70,71], and for USWs, researchers tend to carry out nano/micromotor propulsion in a tailor-made chamber (made from Kapton tape or PDMS) for ultrasound wave reflection and piezoelectric ceramics stuck to the chamber for ultrasound wave generation (Figure 3C,D) [72,73]. Wang et al synthesized nanomotors using gold nanowires (AuNWs) modified with ovalbumin (OVA), which act as model protein antigen.…”
Section: Ultrasound Waves For Propulsionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both surface acoustic waves (SAWs) and ultrasonic standing waves (USWs) can be used for nano/micromotor manipulation. SAWs usually use piezoelectric ceramics (such as lithium niobate, LiNbO3) as the substrate with interdigital transducers (IDTs) on the surface (Figure 3A,B) [70,71], and for USWs, researchers tend to carry out nano/micromotor propulsion in a tailor-made chamber (made from Kapton tape or PDMS) for ultrasound wave reflection and piezoelectric ceramics stuck to the chamber for ultrasound wave generation (Figure 3C,D) [72,73]. Wang et al synthesized nanomotors using gold nanowires (AuNWs) modified with ovalbumin (OVA), which act as model protein antigen.…”
Section: Ultrasound Waves For Propulsionmentioning
confidence: 99%
“…These ultrasound-powered nanomotors help in the process of antigen cross presentation and cellular immunity (with upregulation of MHC I and MHC II-related molecule expression), which are critical components of the immunological effect of therapeutic vaccines for tumors or viral diseases [74]. Cao et al synthesized mesoporous manganese oxide (MnOx) using a water/oil emulsion reaction at room temperature, followed by the loading of indocyanine green derivatives (IDs) [70] with permission, copyright American Chemical Society, Washington, DC, USA, 2023. (B) Schematic illustration showing surface acoustic wave tweezer to remove molecules unbound to micromotors, thus lowering detection limit of cancer-related biomarker miRNA-21.…”
Section: Ultrasound Waves For Propulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2D numerical model of the cross-section of the complete device is considered. 2D models of SSAW devices have been widely reported to study the acoustophoretic phenomenon [ 37 ], to investigate the microchannel behavior [ 45 ], and to compare the performance of hard wall channels with respect to soft wall ones [ 46 ]. Here, a study on the sensitivity of the standing pressure field to variations in the thickness and width of a soft PDMS microchannel cavity is performed as a preliminary step before the fabrication of the device.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Ni et al [ 45 ] already reported different approaches for PDMS modeling in acoustofluidic devices; their analysis highlighted that the modeling of PDMS as an elastic (solid) continuum, supporting the propagation of shear waves, causes specific acoustic streaming effects at the fluid/PDMS interface boundary layer, so that the acoustofluidic problem can be approached more accurately. Considering particles below a certain dimension (typically submicron sized [ 46 ]), the acoustic streaming force has a greater effect on particle manipulation with respect to ARF. In our analyses, due to the considered micrometric size of polystyrene (PS) spherical microbeads, results in terms of their focusing towards the pressure nodes by the acoustic radiation are reported, while the effect of the acoustic streaming is neglected.…”
Section: Introductionmentioning
confidence: 99%